Translation of Sarcasm Found in TILIK Short Movie - Simarmata, Nahoras Bona; Laksmy Ady Kusumoriny (Universitas Cokroaminoto Palopo, 2024)
This research aims at finding sarcasm and translation techniques used to translate them in Tilik short movie. To conduct the research, descriptive qualitative method was applied. The data source of this data is the sarcasm uttered by the characters in the short movie. They are collected based on Camp’s (2011). Meanwhile, the translation techniques were analyzed using Molina & Albir’s (2002). From the research, there were 27 data found to be sarcasm; 14 belong to lexical, 6 belong to proportional, 4 belong to like-prefixed, and the other 3 belong to illocutionary. Meanwhile, from the translation techniques, all the translation of sarcasm in TL show that they were translated using single and couplet techniques. There were 21 data translated using single techniques: compensation (10), modulation (4), literal (3), transposition (2), established equivalent (1), and linguistic compression (1). The other 6 data were translated using couplet techniques; linguistic compression and modulation (3), established equivalent and modulation (1), established equivalent and linguistic amplification (1), and variation and modulation (1). Keywords Sarcasm Translation Techniques Single Techniques Couplet Techniques